2016
DOI: 10.1002/jsc.2079
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of e‐CRM Competitive Advantage on e‐CRM Performance in the Indian Banking Industry

Abstract: e -CRM competitive advantage attained through e-CRM tools and techniques is a positive indicator of the financial and non-financial performance of the banks in India, thereby boosting the overall banks' profitability.In the present scenario, competition is forcing companies to distinguish themselves from their rivals or competitors by offering specialized and efficient services to their customers. It is imperative for the banks in India to implement a comprehensive business strategy for effective service deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Bataineh (2015) stated that E-CRM leads to more satisfied customers with a positive word-of-mouth. In addition, Ismail and Hussin (2013), Kaur (2016), Kaur and Kaur (2016) 2020) also revealed the positive association of E-CRM with customer satisfaction. Therefore, E-CRM services provided by the organizations have allowed the customers to connect and interact with them, which increases their satisfaction level.…”
Section: Hypotheses 221 E-crm and Customer Satisfactionmentioning
confidence: 88%
See 2 more Smart Citations
“…Bataineh (2015) stated that E-CRM leads to more satisfied customers with a positive word-of-mouth. In addition, Ismail and Hussin (2013), Kaur (2016), Kaur and Kaur (2016) 2020) also revealed the positive association of E-CRM with customer satisfaction. Therefore, E-CRM services provided by the organizations have allowed the customers to connect and interact with them, which increases their satisfaction level.…”
Section: Hypotheses 221 E-crm and Customer Satisfactionmentioning
confidence: 88%
“…In addition, the existing literature lacked research on the relationship between E-CRM and consumer satisfaction based on customer experience (Zaim et al, 2020). Numerous studies have also confirmed the relevance of E-CRM in the ebanking industry (Abdulfattah, 2012;Abu-Shanab and Anagreh, 2015;Kaur and Kaur, 2016;Mang'unyi et al, 2018;Al-Dmour et al, 2019;Chuang et al, 2012;Dhingra and Dhingra, 2013;Hendriyani and Raharja, 2018;Paul and Muthumani, 2018;Rashwan et al, 2019;Sharma et al, 2020;Shastri et al, 2020). Also, there were limited studies that assessed the efficacy of E-CRM in the Indian banking industry (Kaur, 2016;Sharma et al, 2020;Shastri et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have shown that any employee satisfaction, technology acceptance and cost play a significant role in the E-CRM inefficiency. Kaur and Kaur (2016) examined that how E‐CRM competitive advantage contributes greatly to financial growth within organizations. The findings of the research have shown that E‐CRM financial performance contributes greatly to organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of firms, competitive advantage is the extent to which a firm is able to create a defensible or superior position over its competitors through its resources and dynamic capabilities [19,32,31]. This study defines competitive advantage of minor export crop farms as using collective actions configured by dynamic capabilities (quality management capability and marketing capability) to keep them separate from their competitors and to keep the farms active and growing.…”
Section: Competitive Advantagementioning
confidence: 99%